Branchial Pathomorphology of Southern Bluefin Tuna Thunnus maccoyii (Castelnau, 1872) Infected by Helminth and Copepodan Parasites - Adams, Mark B.; Hayward, Craig J.; Nowak, Barbara F. (Frontiers in Physiology, 2017)
Three metazoan parasites, a monogenean Hexostoma thynni and two species of copepods Pseudocycnus appendiculatus and Euryphorus brachypterus are known to parasitize the gills of ranched southern bluefin tuna (SBT) and other tuna species. However, there is no detailed information describing the pathological response to infection by these parasites in this species. Wild southern bluefin tuna Thunnus maccoyii (approximately 3 years of age), captured and towed to a grow-out site in the waters immediately south of Port Lincoln, South Australia were subsequently sampled (n = 10) monthly from March until August 2004 during commercial harvest operations. Longitudinal sections of gill hemibranchs with attached parasites were excised and fixed for routine histology and immunohistochemistry. Reference samples were also collected from fish displaying no signs of parasitism or other grossly observable anomalies. Two morphologically distinct granulocytes were observed and putatively identified as eosinophils and mast cells. Pathology was localized to filaments upon and immediately adjacent to parasite attachment sites. Branchial cellular responses, adjunct to the attachment of H. thynni by its opisthaptoral clamps, included hyperplasia and inflammation resulting in structural remodeling of branchial tissues. Inflammatory infiltrates were often dominated by putative eosinophils and lymphocytes when parasitized by H. thynni and P. appendiculatus. Gill associated lymphoid tissue infiltrated the lamellar regions particularly in response to helminth infection. A variable response ranging from hemorrhage with minor hyperplasia or fibroplasia and eosinophilic inflammation to a barely discernible change was seen for gill sections harboring P. appendiculatus and E. brachypterus. The magnitude of the host response to attachment by the latter was congruent with attachment proximity and parasite load. On the basis of the host responses reported here and the low intensity of infection observed in other associated studies these gill ectoparasites are currently considered a low risk for wild and ranched adult SBT.